Ecocide as the Fifth International Crime and the Urgency of Recognition in Indonesian Environmental Criminal Law - Arimbi Fajari Furqon,; Zico Junius Fernando,; Achmad Cholidin, (Proceeding International Conference on Social Sciences, 2026)
This study examines the urgency of recognizing ecocide as the fifth core international crime and its implications for Indonesian environmental criminal law. While the Rome Statute currently recognizes four core crimes genocide, crimes against humanity, war crimes, and the crime of aggression scholars and international movements increasingly advocate for the inclusion of ecocide, considering the scale and severity of environmental destruction. In Indonesia, the enactment of the 2023 Criminal Code has introduced a new configuration of environmental crimes, yet it has not fully addressed the concept of ecocide as a crime of international concern. This research employs a normative legal method, adopting statutory, conceptual, and comparative approaches. The nature of the study is descriptive-prescriptive, aiming both to describe the existing legal framework and to provide recommendations for legal reform. The data collected were analyzed using content analysis to evaluate statutory provisions, doctrinal debates, and comparative legal practices in several jurisdictions. The findings highlight that recognition of ecocide within Indonesian law would not only strengthen environmental protection domestically but also align Indonesia with global efforts to achieve Sustainable Development Goals, particularly in relation to climate action, peace, justice, and the protection of ecosystems.